Emotional Intelligence and Occupational Stress in Romanian Organizations - LEON, Ramona-Diana; TĂNĂSESCU, Ramona Ioana (Management Dynamics in the Knowledge Economy, 2018)
The research aims to analyze the relationship between emotional intelligence and occupational stress in the Romanian banking sector. Therefore, a case study strategy is developed and a quantitative approach is employed. Data are collected from a subsidiary of one of the most profitable banks from Romania and are processed using structural equation modelling – partial least square (SEM-PLS). The results prove that all four dimensions of emotional intelligence have a positive impact on reducing the stress experienced by employees. In other words, those who have a high level of emotional intelligence are less stressed at the workplace; due to the fact that they manage to understand and control their own emotions and the emotions of others, they (i) are more goal-oriented, (ii) focus on what they are doing, and (iii) use their emotions in a constructive way. These findings have both theoretical and practical implications. At the theoretical level, it extends the literature regarding the nexus between emotional intelligence and occupational stress by providing valuable insights from a Romanian banking institution. Furthermore, it helps the policy-makers understand why their employees perceive differently the occupational stress. Besides, it sheds light on how important it is for the managers to develop their ability to recognize their own emotions and using them appropriately in the decision-making processes.